ЕНЕРГОЕФЕКТИВНІСТЬ РЕКУПЕРАТИВНОГО ГАЛЬМУВАННЯ В СИСТЕМАХ ЕЛЕКТРОПОСТАЧАННЯ З РЕГУЛЬОВАНИМИ ЕЛЕКТРОПРИВОДАМИ - Жемеров, Г.Г.; Ільїна, Н.О.; Машура, А.В.; Тугай, Д.В. (Інститут електродинаміки НАН України, Київ, 2018)
Analytical formulas for calculating the maximum possible efficiency of energy supply system with electric regulated drive for three operating modes due to the direction of the energy flow in the system - direct, reverse and bi-directional are obtained. It is shown that even at high values of the energy supply system efficiency in the direct and reverse flows, at high values of the energy return factor, the efficiency in the bi-directional flow can be catastrophically low. References 4, figures 3.